Modelo de implementação de BIM aplicado a projetos de sistemas prediais - Silva Filho, Washington Bastos da (2018)
An appropriate civil construction product development necessarily passes through a design stage, which is often referred as the most strategic stage for improving product quality and reducing production cost. With BIM advent, the design added new responsibilities and significant process changes of architectural and engineering office activities. Although several scientific articles encourage discussions dedicated to modeling construction information for the architecture and the design phase as one, few efforts have been made to deploy BIM in engineering design offices. The MEP design, divided in mechanical, electrical, plumbing and firefighting, make up a significant part of the building model, becoming fundamental to invest in the improvement of this byproduct. However, in Brazil few offices offer their products in BIM, due to the difficulty in implementing the modelling information. Thus, this paper objective to develop a BIM implement model applied to MEP offices. The research method is DSR, Design Science Research, expectancy generating contributions both for scientific knowledge and for the engineering industry. The research begins with theoretical studies on the design stage, MEP systems and BIM technology, focusing on its implementation process. Next, the implementation model was created and applied in a MEP office. During the development of the activity, data were collected from the office staff regarding the application of each step and the model itself. With the outcome of the deployment, the BIM implementation model was redesigned to promote its pragmatic validity. This work is expected to contribute to the expansion of academic knowledge and the application of BIM in buildings production, mainly in the design stage MEP projects.